Work Discipline Analysis of Employee Performance on PT WKB - Shalsabila, Lailatul; Isyanto, Puji; Yani, Dini (Integrasi Sains Media, 2023)
This study was conducted to determine work discipline on the performance of PT WKB. The type of research used in this study is a descriptive analysis method with a qualitative approach—data collection techniques by interviewing and observation. Work discipline is an integral part of the company to achieve employee performance and productivity goals. Lack of discipline can be seen from the working hours of employees who often arrive late, rest at work, and time delays that do not follow the rules at PT WKB. If employee performance decreases, the company also decreases due to employees' lack of discipline. The decrease in work discipline can be seen from absenteeism every month. As for the punitive sanctions in the company's rules, the severity of the punishment greatly determines the good or bad of employee discipline.